The development and evaluation of chitosan-coated enzyme magnetic nanoparticles for cellulose hydrolysis - Park, Heejoon; Johnson, Patrick A. (Frontiers in Chemical Engineering, 2024)
The recycling capability, colloidal and thermal stability of exo-cellulase, endo-cellulase, and β-glucosidases with magnetic particles (MNPs) were evaluated. Co-precipitation and oxidation of Fe(OH)2 methods were used to fabricate magnetic nanoparticles. Three different enzymes were covalently bound to the surface of MNPs using 3-(aminopropyl) triethoxysilane (APTES) and a common protein crosslinking agent, glutaraldehyde. To evaluate the increase in colloidal dispersion stability, chitosan-coating was applied on MNPs and evaluated through particle settlement tests. The results showed that the chitosan-coated MNPs had 3.7 times higher colloidal dispersion stability than the bare MNPs. X-ray photoelectron spectroscopy (XPS) confirmed each magnetic nanoparticle surface modification step and successful enzyme binding. The optimum bioconjugate ratio in exo-cellulase, endo-cellulase, and β-glucosidases was evaluated, and having a high endo-cellulase bioconjugate in the reaction produced the highest glucose. The bioconjugates showed superior glucose productivity 39.4% at 65°C and 22.2% at 88°C in which the native enzyme is inactivated completely after 5 h of exposure. Recycling stability studies showed approximately 78% of activity was retained after 10 cycles and 32% of activity was retained after 20 cycles. The bioconjugates demonstrated equivalent total product conversions as a single reaction of an equivalent amount of the native enzyme after the 10th cycle this work introduces a novel method for covalently binding individual exo-cellulase, endo-cellulase, and β-glucosidases. These bioconjugates showed superior thermal stability and recyclability. It was also demonstrated that chitosan coating significantly improves the colloidal dispersion stability of bioconjugates. Thus this work validates the use of enzyme-MNP bioconjugates to effectively glucose production and promising technique for eventual continuous biological processes.